The influence of LiH and TiH2 on hydrogen storage in MgB2 I: Promotion of bulk hydrogenation at reduced temperature. (1st January 2022) - Snider, J.L.; Liu, Y.-S.; Sawvel, A.M.; Wan, L.F.; Stavila, V.; Mattox, T.M.; Wijeratne, P.; Allendorf, M.D.; Wood, B.C.; Klebanoff, L.E.
Abstract: Mg(BH4 )2 is an attractive hydrogen storage material, owing to its high gravimetric capacity of 14.9 wt %. However, the dehydrogenated material MgB2 is very difficult to rehydrogenate, requiring excessive pressures and temperatures. Here we report the influence of LiH and TiH2 on hydrogen storage reactions involving Bulk MgB2 using XRD, XAS, FTIR and NMR. In ball-milled mixtures of LiH/MgB2, the LiH loses crystallinity but remains undissociated, forming a weakly bound complex with MgB2 . The weak interactions produce minor variations in the local electronic structure at B and Mg, but do not markedly affect the underlying MgB2 hexagonal crystal structure. No evidence is found for a mixed-metal boride Mg1-x Lix B2 in the as-prepared LiH/MgB2 materials. The presence of LiH dramatically improves the hydrogenation of MgB2 at 700 bar, forming borohydride 100 °C below the minimum hydrogenation temperature of pure MgB2 and without the formation of undesirable intermediates such as [B3 H8 ] -, [B10 H10 ] 2- or [B12 H12 ] 2- . Evidence is reported for a mixed-metal borohydride of the type Mg(3-x)/2 Lix (BH4 )3 produced by the hydrogenation. Subsequent desorption is also improved compared to pure Mg(BH4 )2 and LiBH4, showing single-step hydrogen release up to ∼8 wt% by 380 °C, whereas Mg(BH4 )2 and LiBH4 still retain significant amounts of hydrogen at this temperature. The material produced by desorption contains both MgB2 and Mg metal, revealing the original LiH/MgB2 system is not fully reversible. In contrast to LiH, TiH2 is essentially inert when ball-milled with MgB2, and high-pressure hydrogenation leaves only unreacted TiH2 and MgB2 . Thus, added TiH2 provides no benefit to MgB2 hydrogenation. Highlights: Added LiH produces minor variations in the MgB2 electronic structure that promote hydrogenation. LiH improves hydrogenation of MgB2 at 700 bar, forming borohydride 100 °C below the temperature required for pure MgB2 . With added LiH, hydrogenation of MgB2 occurs without the formation of undesirable intermediates. Evidence is reported for a mixed-metal borohydride Mg(3-x)/2 Lix (BH4 )3 produced by the hydrogenation of LiH/MgB2 . Added TiH2 provides no benefit to MgB2 hydrogenation.